Looking for the Best Journey: Real Methodology of Research in General Medicine - Luis Turabian, Jose (International Journal of General Practice, 2018)
The research methods that the researcher uses are one of the most important parts of a study. But, classically, it is said that the initial question must be "What do I need to know and why?" Only after that, you can decide the method that best suits the particular purpose of the study is chosen. But, this article aims to put the "scientific method" in real life in general medicine and primary care, and so the “process of searching for the best research study” is like when we want to find the best time to buy airline tickets: we must look for cheap flights without a date or destination; without a predetermined and invariable research objective. “It's much easier to find deals on flights than hotels.” It is easier to have a research method available (accessible, useful, and possible) than to clearly specify an objective or research topic. There are times when the destination of our trips is based on a good offer of flights. Once we have the method / design, we can decide on the objective to achieve (more modest, grander, etc.). So, be flexible with your objective. When you see a good possibility of conducting a research study, for having the research methods do not let it escape because of the topic or research objective. In research, as in travelling, the adventure is very exciting.
Keywords: Research Methodology; Research Design; General Practice .